Repetitive transcranial magnetic stimulation at low frequency for the treatment of fibromyalgia. Results from the first treatment cohort at the brainwave clinic - Nation, Elliot; Irani, Anushka; Barrett, Stephanie (Frontiers in Pain Research, 2025)
ObjectiveTo assess the clinical effectiveness of low-frequency repetitive transcranial magnetic stimulation (rTMS) in treating fibromyalgia (FM) in a real-world setting.MethodsEighteen adults diagnosed with FM received 20 sessions of low-frequency rTMS over the right dorsolateral prefrontal cortex (DLPFC). Pain and symptom burden were assessed using the Numerical Rating Scale (NRS), Fibromyalgia Impact Questionnaire (FIQ), Sheehan Disability Scale (SDS), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI). Outcomes were compared using paired t-tests.ResultsStatistically significant improvements were observed in NRS, FIQ, BDI, and BAI. A non-significant trend towards reduced disability (SDS) was observed. No serious adverse effects were reported.ConclusionLow-frequency rTMS over the DLPFC shows promise as a safe and effective treatment for FM, improving pain, mood, and impact of FM symptoms, with a trend towards improving disability. Further research with larger cohorts is needed.